Strategi Pembelajaran Problem Based Learning Untuk Meningkatkan Pemahaman dan Pembentukan Karakter Pendidikan Agama Islam - Khayati, Amal; Suhaeni, Heni; Nurhasanah; Ulfah, Elis Siti Maria (Al-Khazin: Jurnal Pendidikan Agama Islam, 2025)
This paper examines the process of character formation in students through the implementation of appropriate learning models within Islamic Education. The study is motivated by the increasing complexity of national character issues that emerge across various sectors, including educational environments, socio-religious settings, and governmental institutions. This research employs a qualitative approach using library research methods, analyzing relevant literature on Problem Based Learning (PBL) and character development in Islamic Education through descriptive analysis. The findings indicate that educational institutions must provide strategic solutions to address character-related problems among students. One recommended approach is Problem Based Learning (PBL). PBL has been shown to enhance students’ understanding of Islamic Education values while fostering positive character traits such as religiosity, responsibility, hard work, independence, democracy, tolerance, environmental awareness, socio-religious care, and patriotism. Through the use of real-life problem-solving activities, PBL encourages students to internalize moral and spiritual values more contextually and deeply, leading to more effective and sustainable character formation.